The Relationship Between Intelligence and Learning Motivation on Childrens With Special Need in Inclusive Elementary School - Komarudin, Komarudin (Universitas Muhammadiyah Metro, 2017)
The research aimed to find out the corelation between intelligence and learning motivation in children with special need in inclusion elementary school. The data collecting technique used the learning motivation scale and Slosson Full Range Intelligence Test (S-FRIT). The data were analysed by used product moment correlation technique with SPSS 16. The data analysis result was correlation coefficient was 0.581 with a significance level of 0.000 (p <0.05). It meant there was positive correlation between intelligence and learning motivation. The higher level of intelligence, the learning motivation is also higher; conversely the lower level of intelligence, the learning motivation is also lower. The coefficient determination was 0.337 contributing intelligence to improvement learning motivation was 33.70%. This suggests that 66.30% learning motivation subjects influenced by other factors which not included in this research.Â